2017
DOI: 10.1111/jeb.13175
|View full text |Cite
|
Sign up to set email alerts
|

Escape from predators and genetic variance in birds

Abstract: Predation is a common cause of death in numerous organisms, and a host of antipredator defences have evolved. Such defences often have a genetic background as shown by significant heritability and microevolutionary responses towards weaker defences in the absence of predators. Flight initiation distance (FID) is the distance at which an individual animal takes flight when approached by a human, and hence, it reflects the life-history compromise between risk of predation and the benefits of foraging. Here, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…First, behavior toward humans may not necessarily be a reliable indicator of overall anti‐predator behavior (Seress & Liker, ). Several studies treat the two as equivalents, generalizing responses to humans as an estimate of responses to any kind of predator (Jiang & Møller, ; Michelangeli, Chapple, Goulet, Bertram, & Wong, ; Møller, ; Møller & Ibáñez‐Álamo, ; Møller, Vágási, & Pap, ). Our results suggest that responses to humans and to non‐human predators do not necessarily covary; thus, we need to be careful with this kind of interpretation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, behavior toward humans may not necessarily be a reliable indicator of overall anti‐predator behavior (Seress & Liker, ). Several studies treat the two as equivalents, generalizing responses to humans as an estimate of responses to any kind of predator (Jiang & Møller, ; Michelangeli, Chapple, Goulet, Bertram, & Wong, ; Møller, ; Møller & Ibáñez‐Álamo, ; Møller, Vágási, & Pap, ). Our results suggest that responses to humans and to non‐human predators do not necessarily covary; thus, we need to be careful with this kind of interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between responses to humans and responses to non‐human predators is often considered to be particularly strong, as it is frequently assumed that animals perceive humans as a type of predator (Beale & Monaghan, ; Frid & Dill, ). Consequently, some authors interpret responses toward humans as a measure of general anti‐predator response (Stankowich & Blumstein, ); for example, they consider the relatively low flight initiation distances (Jiang & Møller, ; Møller, ) and higher docility during handling (Møller & Ibáñez‐Álamo, ) by urban compared to non‐urban birds as decreased general anti‐predator behavior. This “general risk‐taking” hypothesis predicts that as animals increase their risk‐taking toward humans in urban habitats, their risk‐taking toward non‐human predators also becomes greater (Geffroy et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that our predictors have certain limitations because birds' behaviour is affected by inherent genetic characteristics such as temperament and physiological properties [60]. Species could be a relatively important factor in explaining variations in FID [50].…”
Section: The Predictors Of Birds' Fid Among Environmental Characteris...mentioning
confidence: 99%
“…The presence of pike predators clearly increased salmon mortality, suggesting that predator avoidance skills were decisive for survival. Low genetic diversity has previously been associated with decreased predator avoidance (Auld & Relyea, 2010; Jiang & Møller, 2017; Møller & Nielsen, 2015). However, in the present study, LS had the lowest mortality, while the hybrids showed 21–26% higher predation risk.…”
Section: Discussionmentioning
confidence: 99%
“…This requires cognitive skills for predator detection as well as physiological, behavioral or morphological defense traits, all of which could be hampered in small and declining populations. For example, avian prey species with low genetic diversity are known to display reduced antipredator behavior (Jiang & Møller, 2017) and experience a higher risk of predation (Møller & Nielsen, 2015). Further, inbreeding reduces the ability of Physa acuta snails to plastically respond to changing predation risks (Auld & Relyea, 2010).…”
Section: Introductionmentioning
confidence: 99%